Renal lesions in deer (Cervus elaphus): involvement of Mycobacterium avium Subsp. paratuberculosis - Matos, Ana Cristina (2013)
In Europe, paratuberculosis infection has been described in red deer (Cervus elaphus). Mycobacterium avium subsp. paratuberculosis (MAP) in kidneys was previously reported in cows with advanced paratuberculosis; however, it has not been identified in wild deer.